Osteopontin's relationship with malnutrition and oxidative stress in adolescents. A pilot study. - Octavio Gamaliel Aztatzi-Aguilar (Public Library of Science (PLoS), 2021)
Osteopontin (OPN) is a protein involved in inflammatory illnesses such as fibrosis and cancer; its overexpression in cardiovascular diseases promotes the biomineralization of blood vessels and other soft tissues. Moreover, there is an active component of oxidative stress related with those diseases. The present study relates serum OPN levels with nutritional condition and oxidative stress in a group of adolescents. Anthropometric measurements were performed, and fasting blood samples were analyzed to determine OPN concentrations, blood chemistry parameters (glucose, triglycerides, total cholesterol, urea, uric acid, and creatinine) and oxidative stress biomarkers (Paraoxonase-1, Glutathione S-Transferase, Catalase, NAD(P)H Quinone Oxidoreductase, free carbonyl groups and malondialdehyde). Adolescents were categorized according to body mass index (BMI) and metabolic syndrome (MetS) criteria. We found increased OPN serum concentrations in overweight and obese adolescents, as well as in adolescents with MetS. Rises in OPN correlated with arm circumference and biomarkers of lipid peroxidation; with regard to serum glucose there was a trend to positive correlation. Our results suggest that serum OPN is associated to nutritional status and could be considered as an early biomarker of low-grade inflammation and probably the early biomineralization of soft tissues in adolescence.